History and Prospects of Sustainable Textile Architecture - Al-Azzawi, Rana Alaa Shareef; Al-Alwan, Hoda A. S. (Technological Innovation in Engineering Research Vol. 4, 2022)
Textiles are increasingly used in a variety of industries, including the construction industry. Because of their numerous distinctive properties, such as being lightweight, low cost, and durable, as well as delivering low energy consumption, flexibility, and resilience, "Textile Architecture" and "Fabric Structures" are acquiring new popularity in the construction world. Fabric structures have been utilized throughout history, beginning with the first tents created by humans to give shelter from harsh weather conditions when natural shelters were unavailable, and continuing to the current day, with structures that have been elaborated to fulfill the needs of increasingly complicated applications in various forms, shapes, and sizes. The purpose of this article is to examine the history of textile architecture, and to shed light on the wide range of contemporary modern uses and architectural applications, as well as to highlight the unique sustainable architecture's future prospects. The paper employs a descriptive research technique to trace the evolution of such structures in order to shed light on recent global developments in the field of architecture in terms of developing excellent sustainable designs and technical solutions that use textiles.